Cameroon : Staff Report for the 2012 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2012)
Despite achieving macroeconomic stability, there is not much improvement in Cameroon's social indicators. To achieve higher and more inclusive growth, the report mentioned that problems in sectors such as infrastructure and a reduction in per capita income and mounting costs of fuel subsidies should be attended to. Due diligence should be exercised to control the expenditure chain and to better track the flow of funds. Better cooperation between national and regional bodies should be initiated for financial stability.